Facebook and the changing consumer culture among university students A field study on a sample of students from the Department of Sociology at Constantine University 2 - نورالدين بن الشيخ (International Journal of Social Communication, 2025)
This article aims to shed light on the impact of Face book on changing the consumption culture among university students through a field study conducted on a sample of 164 students from the Department of Sociology at the University of Constantine 2. The descriptive method was used in this study, and a questionnaire form was applied. The study concluded that Face book played a significant role in changing purchasing values and monthly spending areas among university students.